Improving Rural Mobility : Options for Developing Motorized and Nonmotorized Transport in Rural Areas - Starkey, Paul; Ellis, Simon; Hine, John; Ternell, Anna (Washington, DC: World Bank, 2013)
Many inhabitants of rural areas in developing countries lack adequate and affordable access to transport infrastructure and services. Improving rural people's access to essential services requires better mobility through transport infrastructure and services as well as the location, price, and quality of facilities. This report focuses on improving rural mobility by facilitating the provision of affordable means of transport and transport services. To deliver significant economic and social benefits, investment in transport must take an integrated approach. Rather than focusing solely on expanding road networks, it should also pay attention to smaller roads, paths, and tracks; the use of private and commercial means of transport; and the importance of transport hubs and markets. Transport planners need to take a holistic approach that involves all stakeholders in a participatory process of assessing needs within a clear policy framework based on the interdependence and complementarity of different means of transport. In addition, favorable policies and operating environments can enable the private sector and nongovernmental organizations to play important roles in new initiatives. Pilots can be used to promote lower technology, intermediate means of transport. The needs of women and disadvantaged groups should be considered during planning. Monitoring and evaluation involving stakeholders are also important.